The Effects of Family Functioning Dimensions on the Subjective Wellbeing among High School Students - Hafshoh, Hafshoh; Saleh, Airin Yustikarini (UI Scholars Hub, 2021)
Subjective well-being in school offers myriad benefits for the overall development and well-being of students and is thus crucial. This study examines the effects of the family functioning dimensions of cohesion, flexibility, and communication on subjective well-being displayed by students on school premises. An aggregate of 475 students from five high schools in Greater Jakarta participated in this study. The Brief Adolescents’ Subjective Well-Being in School Scale was administered to measure subjective well-being in school. The Family Adaptability and Cohesion Evaluation Scale and the Family Communication Scale were employed to measure family functioning. The results revealed that family flexibility and family communication positively and significantly affected the subjective well-being of students. Family communication exerted a more substantial influence than the other dimensions of family functioning because it could enhance the other dimensions. Prospective studies should investigate more specific student characteristics, such as living independently without parents or living with a single parent.